Singapore on the Thames : Model for a Post-Brexit UK? - Martin, David (2020)
Last week, the UK formally exited the European Union. As it charts a new destiny outside the EU post-Brexit, the domestic debate is whether it should adopt the Singapore model of economic self-reliance. Can ‘Singapore on the Thames’ work?